Socio-environmental success or failure of Extractive Reserves in the Amazon? (Research, Society and Development, 2021)
Brazilian public institutions have difficulties in building relationships of trust that truly promote sustainable development. This study proves that the Extractive Reserves (RESEX) socio-environmental crisis occurs due to the interdependent relationship that exists between environmental, economic, social groups and institutional organizations. The study concludes that the implementation of public policies regarding health, education, transportation, communication, technical assistance, energy, as well as the current revenues from the productive activities of extractivism, agriculture, and cattle ranching was ineffective, because the state did not cooperate with strategies to alleviate the conflict between conservation and development.